Pore pressure pulse migration in microcracked andesite recorded with fibre optic sensors. (December 2020) - Nicolas, A.; Blöcher, G.; Kluge, C.; Li, Z.; Hofmann, H.; Pei, L.; Milsch, H.; Fortin, J.; Guéguen, Y.
Abstract: Pore pressure has a major influence on the effective stress and thus on the mechanical behaviour of rocks. In this study, we focus on the hydro-mechanical behaviour of a low porosity andesitic rock heat-treated to 930 °C to induce thermal cracks and increase the permeability of the samples. First, we show that permeability decreases from 8 × 10 −16 m 2 to 1.5 × 10 −17 m 2 with a confining pressure (P c ) increase from 2 MPa to 40 MPa (pore pressure being approximately 0.2 MPa). Then, we used fibre optic pressure sensors to monitor pore pressure diffusion at three points along the sample during the propagation of a pore pressure pulse under hydrostatic (P c = 40 MPa) and triaxial stresses (P c = 40 MPa, differential stress of 356 MPa). When the pore pressure pulse was applied, the fibre optic sensors showed a sudden pore pressure increase one after the other as a function of their location along the sample. Pore pressure increase downstream was very smooth under hydrostatic stress and almost zero after the duration of the experiment (50 min) under triaxial stresses. This lack of downstream pore pressure increase under triaxial stresses is due to the fact that a differential stress of 356 MPa decreased permeability from approximately 1 0 − 17 m 2 to approximately 1 0 − 19 m 2 . Finally, the pore pressure diffusion process was modelled considering a uniform spatial distribution of permeability in the andesite sample and the dead volume attached at the downstream side. Highlights: We record pore pressure migration in low permeability rock with fibre optic sensors. Permeability decreases by two orders of magnitude with increasing pressure. Permeability is likely to vary as a pore pressure pulse migrates along the sample. However, results can be modelled with diffusion equation under constant permeability.